Pengaruh Profitabilitas, Leverage, dan Likuiditas terhadap Agresivitas Pajak dengan Komisaris Independen sebagai variabel Moderating pada Perusahaan Manufaktur di BEI tahun 2016-2020 - Munawar Munawar; Ajeng Luthfiyatul Farida; Ratih Kumala; Desyi Erawati (Owner : Riset dan Jurnal Akuntansi, 2022)
Taxes are the largest source of state revenue. The government is trying to increase tax revenue every year to meet state spending. In the company's prespectives, taxes are considered a burden. This of course requires companies to carry out tax aggressiveness,such as doing many ways in order to minimize tax payments. Literature study shows that there are many factors that influence tax aggressiveness. This research had the aim of analyzing the effect of profitability (ROA), Leverage, and Liquidity (CR) on tax aggressiveness. The researcher uses the independent commissioner variable as a moderator, the population is a manufacturing company in the consumer goods sector listed on the Indonesia Stock Exchange. The sample was selected using a purposive sampling method. Based on the conditions that have been determined by the author. There are 26 samples of consumer goods sub-sector manufacturing companies listed on the Indonesia Stock Exchange 2016 – 2020. The results of data processing concluded that partially significant ROA has an effect on tax aggressiveness, partially Leverage has no significant effect on tax aggressiveness, while CR partially has an insignificant and insignificant effect on tax aggressiveness. Independent Commissioner weakens the influence of Leverage on tax aggressiveness. Independent Commissioner strengthens the influence of ROA and CR on tax aggressiveness